2022
DOI: 10.3389/fpubh.2022.1070334
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram of suicidal ideation among men who have sex with men in China: Based on the integrated motivational-volitional model of suicidal behavior

Abstract: IntroductionMen who have sex with men (MSM) are a high-risk group for suicide, with a much higher prevalence of suicidal ideation (SI) than the general population and male population. The aim of this study was to explore the risk factors influencing the development of SI and to develop and validate a nomogram among MSM.MethodsA cross-sectional study was conducted in 915 MSM from Shanghai, Shenyang, Shenzhen and Kunming, China using the snowball sampling method. The integrated motivational-volitional (IMV) mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…Our findings suggested that depression is associated with suicidal ideation among HIV-positive MSM, which is consistent with the previous studies conducted in Shenzhen, Shenyang, Anhui, et al [ 11 , 19 , 38 ]. Mu et al revealed that mental disorders represented by depression constitute the largest reason for suicidal behavior in Chinese MSM [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings suggested that depression is associated with suicidal ideation among HIV-positive MSM, which is consistent with the previous studies conducted in Shenzhen, Shenyang, Anhui, et al [ 11 , 19 , 38 ]. Mu et al revealed that mental disorders represented by depression constitute the largest reason for suicidal behavior in Chinese MSM [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of suicidal ideation among MSM may differ by age, educational level, economic level, high-risk sexual behaviors, and attitudes towards sexual minorities [ 8 , 11 ]. In addition, the previous studies also demonstrated that suicidal ideation was associated with depression and HIV-related stigma among HIV-positive MSM [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation